8. PERANCANGAN GAME EDUKASI My Sunsun UNTUK MOTIVASI CINTA LINGKUNGAN DENGAN MENGGUNAKAN SCIRRA CONSTRUCT2 - Jumblath, Kamal; Hamdan, Dani (SISKOM, 2018)
The development of information and communication technology currently has a big influence on various aspects of life, even human behavior and activity is now much dependent on information and communication technology. One example is the use of technology in teaching and learning process, especially multimedia computer technology. In the world of education, various multimedia-based learning media is being developed, to help create an effective and interesting learning process. One form of multimedia-based learning media is educational games. Educational games are chosen because the game as a visual medium has advantages compared to other visual media because the game invites players to participate and share in determining the end result of the game. This game will invite players, especially early child to know the type of garbage. Stages in this design process are basic idea, story line, graphic design, sound, determining gameplay control, and testing. After the design procedure and running accordingly, and the media meet the appropriate interactive criteria, just done conversi from html5 to the android platform to run on a smartphone. With the educational game love the environment as a child's learning media using this construct2 scirra, it is expected to attract children to love and preserve the environment. So it is expected to boost the love of nature and around by making the garbage in its place according to the type of garbage.